FENOMENA PEKERJA ANAK USIA SEKOLAH - S Wisni Septiarti (LPPM UNY, 2002)
Abstract This research was aimed to covered the phenomenon of school age workers by seeing cause factors that involving them in public economic activity, patterns of study and work, and also what kind of social treatments which they received. The research, which used qualitative analysis in urban and rural areas, found that the 35 school age workers in this research lost their cheerful childhood when they had to devise their time to work and study. Then helping to lighten the economic burden in a family, environmental or peers influences were the two classical reasons of school age workers to decide to involve in the economic activities. School age workers met the problem emerged from the wrong treatment of adults who exploit their power on purpose. The exploitation of child workers, both direct or indirect experiences, and the wrong treatments they received influenced on the deviation of behavior of school age workers. The deviation of behavior occurs in the urban area which tend to get better social treatments in the improvement of their knowledge, skills and spiritual building. Keywords: school age worker, pattern of study and work, social treatments